Bactrodesmium uniseptatum, nom. nov.: a replacement name for the later homonym B. amazonicum P.R.Silva & Gusmão (Dothideomycetes, incertae sedis) - Gusmão, Luís Fernando Pascholati; Barbosa, Flavia Rodrigues (Phytotaxa, 2026)
N/A